2002
DOI: 10.2190/vrd4-69af-wpq6-p734
|View full text |Cite
|
Sign up to set email alerts
|

All-Female Classes in High School Computer Science: Positive Effects in Three Years of Data

Abstract: In a three-year study, female students from all-female computer science (CS) classes were compared to male and female students from mixed-gender CS classes. Participants were 250 students enrolled in an elective Grade 11 CS course (63 females from three all-female classes and 155 males and 32 females from nine mixed-gender classes). Participants completed a questionnaire assessing perceived support from teachers and parents, computer-related attitudes, and future academic and occupational intentions. Females f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…They suggest that single-sex classes have the potential to raise the achievement of both boys and girls and to have a positive influence on learning climate but only if "developed within gender relational contexts" (Younger and Warrington 2006, 579) -that is, in ways which challenge existing gender stereotypes. A study of all-female computer science classes revealed positive effects on achievement (Crombie et al 2002) as did single-sex physics variety of statistical techniques (including multilevel modelling) but any such techniques will not solve the problem of comparison if the two sectors are very different indeed. Researchers have also differed about the kinds of variables to be controlled for in looking at the net impact of single-sex grouping.…”
Section: Resultsmentioning
confidence: 99%
“…They suggest that single-sex classes have the potential to raise the achievement of both boys and girls and to have a positive influence on learning climate but only if "developed within gender relational contexts" (Younger and Warrington 2006, 579) -that is, in ways which challenge existing gender stereotypes. A study of all-female computer science classes revealed positive effects on achievement (Crombie et al 2002) as did single-sex physics variety of statistical techniques (including multilevel modelling) but any such techniques will not solve the problem of comparison if the two sectors are very different indeed. Researchers have also differed about the kinds of variables to be controlled for in looking at the net impact of single-sex grouping.…”
Section: Resultsmentioning
confidence: 99%
“…There is some evidence that knowledge gains can be made from informal learning when several visits are made over an extended period of time . Objective measures of grades and success can provide hard evidence about the impact of informal education (e. g …”
Section: Discussionmentioning
confidence: 99%
“…Au sein de l'article « Co-education and gender: the end of the experiment? », Clark (2004) conclut qu'au regard des différents travaux réalisés sur ce sujet (Crombie, Arbarbanel & Trinneer, 2002 ;Gillibrand, Robinson, Brawn et al, 1999 ;Jackson, 2002 ;Stables, 1990 ;Younger & Warrington, 2002), la non-mixité favorise une meilleure estime de soi chez les adolescentes alors que la mixité tend à renforcer les rôles de genre dans des disciplines telles que les mathématiques ou les sciences.…”
Section: La Non-mixité à L'école : Des Effets Plutôt Positifs Sur Launclassified